2017
DOI: 10.1007/978-3-319-60639-2_2
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Recognition Using Physiological Signals: Laboratory vs. Wearable Sensors

Abstract: Emotion recognition is an important research topic. Physiological signals seem to be an appropriate way for emotion recognition and specific sensors are required to collect these data. Therefore, laboratory sensors are commonly used while the number of wearable devices including similar physiological sensors is growing up. Many studies have been completed to evaluate the signal quality obtained by these sensors but without focusing on their emotion recognition capabilities. In the current study, Machine Learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 13 publications
6
65
0
Order By: Relevance
“…Alternatively, this result may suggest that higher stimulations of the sympathetic nervous system are needed for observing responses in wrist SC. This interpretation is in line with preliminary studies on the E4 SC signal, suggesting its relatively high sensitivity to emotional stress (Ollander et al, ; Ragot et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Alternatively, this result may suggest that higher stimulations of the sympathetic nervous system are needed for observing responses in wrist SC. This interpretation is in line with preliminary studies on the E4 SC signal, suggesting its relatively high sensitivity to emotional stress (Ollander et al, ; Ragot et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, most PPG sensors have shown a satisfactory accuracy only in restricted conditions, such as at rest in absence of motion (Schäfer & Vagedes, 2013). The accuracy of the E4 wristband has been assessed by only a few preliminary studies, mainly focused on stress and emotion recognition (e.g., Ragot, Martin, Em, Pallamin, & Diverrez, 2017). Two studies focused on the PPG signal and suggested satisfactory data quality (McCarthy, Pradhan, Redpath, & Adler, 2016) and acceptable measurement error in mean HR and some HRV measures (Pietilä et al, 2017).…”
mentioning
confidence: 99%
“…One study combined GSR and PPG, collected by a Shimmer3 sensor [24], to classify High/Low valence and arousal [25]. In another study, unimodal PPG data collected by an expensive wrist-worn wearable device (Empatica E4 [26]) was compared with data collected by a laboratory sensor (Biopac MP150 [27]) [28]. Although these studies represent an important step towards real-world applicability, we are not aware of any studies that have explored emotion recognition using IBI PPG data of the type collected by affordable consumer fitness trackers.…”
Section: B Emotion Prediction From Unimodal Ppg Datamentioning
confidence: 99%
“…For example, it requires more effort and time for researchers to place the electrodes on participants’ arms, face, and fingers, than to wear the wearable device. Importantly, they can measure psychophysiological signals continuously while people go about their daily lives (Garbarino, Lai, Bender, Picard, & Tognetti, ; Ragot, Martin, Em, Pallamin, & Diverrez, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, skin conductivity (SC) signals again showed low correlation between the two types of devices. Recently, Ragot and colleagues () compared physiological data from the E4 wristband to those of laboratory equipment (Biopac) during an emotion recognition experiment (using emotional pictures). These authors utilized machine learning models for the analysis of their psychophysiological data and found that the mean responses of physiological data (for cardiac features of HR, AVNN, SDNN, RMSSD, pNN50, LF, HF, RF) yielded from the wearable device, were similar to those of the laboratory equipment.…”
Section: Introductionmentioning
confidence: 99%